Prescription Analysis for Variation in the Cost of Different Brands of Same Medicine for the Treatment of Depression at a Tertiary Hospital of Nepal - Khadka, Anjan; Manandhar, Pradeep; Katuwal, Nagendra; Khatri, Mahesh (Birat Journal of Health Sciences, 2020)
Introduction: Depression often remains unrecognized, misdiagnosed and/or under treated. There are multiple drugs from multiple companies which are available for treatment of depression. The prices of same drug with different brands are variable which questions the afford ability of treatment to the patients and their compliance.Objective The study was conducted to analyze the cost variation of different brands of antidepressant drugs prescribed in a tertiary care hospital of Nepal.Methodology This study design was cross-sectional and method was quantitative method and conducted at department of pharmacology of a tertiary care hospital from September 2018 to January 2019 after getting approval from institutional review committee. The commonly prescribed antidepressant drugs were recorded from prescription records of department of psychiatry and their cost, cost ratio and percentage variation were calculated as per current index of medical specialties and National index of medical specialties. The data were recorded in MS excel and presented as simple descriptive statistics.Result The study included seven commonly prescribed antidepressants obtained from 214 prescription records. The cost of one course of citalopram 40 mg tablet was found to be higher and the cost of one course of imipramine 25 mg tablet was found to be lower. The maximum and minimum cost ratio was 2.46 and 1.08 with fluoxetine 20 mg capsule and dothiepin 50 mg tablet respectively. The maximum and minimum percentage of cost variation was with fluoxetine 20 mg capsule and dothiepin 50 mg tablet.Conclusion Costs of antidepressants had wider variations depending on the manufacturers and availability of different dose and brands.